2021
DOI: 10.1017/jfm.2020.1017
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquity of particle–vortex interactions in turbulent counterflow of superfluid helium

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…Švančara et al. (2021), for the estimate of we employed the Stokes formula, assuming spherical particles with radius equal to m (the density of solid deuterium is set to , and the fluid temperature is set to K).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Švančara et al. (2021), for the estimate of we employed the Stokes formula, assuming spherical particles with radius equal to m (the density of solid deuterium is set to , and the fluid temperature is set to K).…”
Section: Resultsmentioning
confidence: 99%
“…We employ specifically the particle tracking velocimetry technique, which is based on following the flow-induced motions of relatively small particles – see Švančara et al. (2021) for another recent example. Our -sized particles are made of solid deuterium; they are illuminated with a mm thick laser sheet crossing the symmetry axis of the set-up, and their motion is captured by a high-speed digital camera with a narrow depth of field.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Švančara et al. 2021). More generally, our work neatly demonstrates that quantitative comparisons between particle trajectories obtained under different experimental conditions can be performed using pseudovorticity maps, taking also into account particle concentration and inertia.…”
Section: Discussionmentioning
confidence: 98%
“…The cryogenic flows of this unique liquid are routinely visualized and several PTV studies have been reported to date – see Švančara et al. (2021) for a recent example. However, at a given time, one can usually identify the positions of about 100 particles within a 1 Mpixel image, each particle having an apparent size of a few pixels.…”
Section: Introductionmentioning
confidence: 99%